Pengaruh Pelatihan dan Pengembangan SDM Terhadap Kinerja Karyawan Klinik Chio Medical Center Karawang - Rustawan, Nadia Dwi Rijki; Hidayat, Arif; Partimah, Partimah (YUME : Journal of Management, 2024)
This research was conducted at the Chio Medical Center Karawang Clinic with the aim of the research being to determine and analyze the influence of HR training and development on the performance of Chio Medical Center clinic employees. The method used in this research was quantitative using a questionnaire as a data collection tool which was distributed to respondents with a sample as many as 40 people. The Influence of HR Training and Development on the Performance of Chio Medical Center Clinic Employees by looking at the results of the t test on the training variable, the calculated t value (2.174) is greater than the t table value (1.994) so that based on the t test criteria, H1 is accepted. Apart from that, it is known that the significance value is (0.036) <0.05, so it is known that the effect is significant. So it can be concluded that there is a positive and significant influence between training on employee performance at the Chio Medical Center Clinic. Then for the HR development variable, the calculated t value (3.237) is greater than the t table value (1.994) and the significance value is 0.003 < 0.05 so that based on the t test criteria, H1 is accepted. So it can be concluded that there is a positive and significant influence between HR development on employee performance at the Chio Medical Center Clinic.